Solvability of boundary value problems for the general Schrödinger equation via Schrödinger-type identity methods. (July 2020) - Chen, Mei; Zhu, Xia
Abstract: In this article we consider a free boundary value problem for the general Schrödinger equations with density-dependent viscosity coefficients by applying a powerful technique based on the Schrödinger-type identity method. Under certain assumptions imposed on the initial data, there exists a unique solution for this equation mentioned above. Finally, we also give an application, which reveals that the Schrödinger-type identity method is effective and simple.